1984
DOI: 10.1159/000172928
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function during Decreased Perfusion Pressure Due to Aortic Clamping and Hemorrhagic Hypotension: A Single Nephron Study in Dog Kidney

Abstract: Whole kidney and single nephron function was compared in dogs during a stepwise lowering of renal perfusion pressure (PP) induced by aortic clamping (C) or hemorrhagic hypotension (HH). In C, renal vascular resistance (RVR) decreased with decreasing PP, the decrease being due to a drop in afferent resistance (RA) only. HH was associated with a rise in RVR due in the first phase mainly to an increase in RE, later to both RA and RE. There was a decrease in total kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…The two decades of experience in micropuncturing the dog kidney are probably the reason why our results now, despite the principal similarity, are superior (with regard to the scatter of data) to our earlier experiments (Heller & Horacek, 1984). Thus, although the Kf value showed 'a surprising tendency to rise' (Shirley & Walter, 1995) in our earlier paper, this nonsignificant tendency is not present now.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The two decades of experience in micropuncturing the dog kidney are probably the reason why our results now, despite the principal similarity, are superior (with regard to the scatter of data) to our earlier experiments (Heller & Horacek, 1984). Thus, although the Kf value showed 'a surprising tendency to rise' (Shirley & Walter, 1995) in our earlier paper, this nonsignificant tendency is not present now.…”
Section: Discussioncontrasting
confidence: 54%
“…We have shown previously (Heller & Horacek, 1984) that this vasoconstriction during mild HH is more pronounced in the efferent than in the afferent arteriole; this difference disappears as HH progresses. These findings of ours were recently criticized (Shirley &Walter, 1995) for using an indirect approach based on a number of challengeable assumptions.…”
Section: Introductionmentioning
confidence: 73%
“…Another factor contributing to the limited proximal tubular response 628 might be a fall in colloid osmotic pressure in peritubular capillaries: plasma protein concentration is reduced following haemorrhage as a result of the rapid entry of interstitial fluid into the vascular compartment (Bealer, 1986;Shirley et al 1991). However, although direct evidence exists for a reduced colloid osmotic pressure in efferent arterioles following haemorrhage (Heller & Horacek, 1984), the same study also reported a fall in peritubular capillary hydrostatic pressure. The net change in peritubular physical factors is therefore likely to be small.…”
Section: Resultsmentioning
confidence: 98%
“…In the one detailed study of glomerular dynamics that has been performed (in dogs), Heller & Horacek (1984) found that stepwise haemorrhage-induced reductions in blood pressure caused stepwise reductions in glomerular capillary pressure, although there was a surprising tendency for the calculated ultrafiltration coefficient to rise. Computed values for both afferent and efferent arteriolar resistances increased after haemorrhage, but these calculations were very indirect and based on a number of challengeable assumptions; they therefore provide little clue to the mechanisms involved.…”
Section: Resultsmentioning
confidence: 99%
“…These were described in detail previously [17,18]. Briefly, femoral vessels and both ureters were cannulated for BP monitoring, i.v.…”
Section: Experimental Techniquesmentioning
confidence: 99%